Flash Spark Plasma Sintering of 3YSZ: Modified sintering pathway and impact on grain boundary formation. Issue 15 (December 2021) - Hérisson de Beauvoir, Thomas; Ghomari, Zakaria; Chevallier, Geoffroy; Flaureau, Andréas; Weibel, Alicia; Elissalde, Catherine; Mauvy, Fabrice; Chaim, Rachman; Estournès, Claude
Abstract: Yttria stabilized zirconia (3 mol% YSZ) ceramics were prepared by Flash-SPS, while allowing high heating rates up to 200 °C/s, which led to the extremely fast densification within a few seconds. The high heating rates had strong impact on sintering mechanisms, in terms of densification and grain growth. While the specimens ended with 5–15 vol% porosity and limited grain growth (< 350 nm), their hardness is higher than fully dense counterpart SPSed ceramics. Using the sintering trajectories, microstructural observations, and impedance spectroscopy, we highlight altered sintering mechanism which resulted in very thin grain boundaries compared to SPS. It appears that densification is largely advanced at grain boundary interfaces, with no residual nano-pores at the grain junctions, where some pores with size comparable to grain size were present. This opens up opportunities for the fabrication of porous lightweight ceramics with good mechanical properties.